Anti-Bullying Strategies in Pesantren Affiliated with Universities: A Case Study of Women’s Protection Policies at Ma’had Al-Jami’ah Walisongo - Azwa Qonitatun; Mustopa Mustopa; Alifa Rizki Kaila Ainur Rohmah; Sahra Naura Luwistiana; Zulfasa Kaila Yuniasih; Adilet Zhagypar (Journal of Islamic Education Thought and Development, 2026)
The main objective of this study is to analyze in depth the implementation and effectiveness of anti-bullying strategies for women at Ma'had Al-Jami'ah UIN Walisongo to ensure the psychological safety of female students. Using a qualitative approach with a case study design, empirical data were collected through unstructured interviews, participatory observation, and document analysis at the research location, then analyzed using the Miles and Huberman interactive model. The research findings reveal significant synergy between formal policies and social realities in the field. Strict regulations and case handling Standard Operating Procedures (SOPs) have been implemented consistently, supported by a positive seniority culture normalized in the name of character education and mental mentoring. The role of supervisors appears highly proactive; they function as firm yet inclusive protectors, making the prevention function sharp due to systemic assertiveness. The strategy is deemed effective because it is preventive in nature, the reporting mechanism is trusted by victims due to confidentiality guarantees, and sanctions provide constructive educational effects. The majority of incidents are well-handled, creating a real sense of security for the university's central management. Female students feel safe in private dormitory areas thanks to written rules that are enforced fairly. The prevention cycle continues with meaningful institutional learning. These findings confirm that rules accompanied by consistent execution commitment and a supportive organizational culture are capable of ensuring real protection. Systemic sustainability in internal law enforcement and supervisor training is needed to maintain continuous protection for female students. The contribution of this research lies in uncovering specific institutional integration mechanisms in hybrid religious education that provide a new analytical framework for understanding the success of anti-bullying strategies comprehensively, as well as important policy recommendations for stakeholders.